2015
DOI: 10.7314/apjcp.2015.16.11.4705
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration and Its Correlates among Cancer Survivors in Korea: the Korea National Health and Nutrition Examination Surveys

Abstract: Background: Though a large proportion of cancer survivors are assumed to be commonly affected by sleep disturbance, few studies have focused on short sleep problems and its correlates among Korean cancer survivors. The purpose of this study was to evaluate the prevalence of short sleep in adult cancer survivors from a nationwide population-based sample and to identify risk factors for short sleep duration. Materials and Methods: Based on the fourth and fifth Korea National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…Petrov et al (2014) found that 9.6% of their subjects used prescribed sleep medications and 11.1% used over-the-counter sleep aids [ 90 ]. Analogous to other investigations, where cancer patients presented sleep disturbances after cancer diagnosis and treatment [ 91 ], both cancer groups of our study significantly increased the consumption of sleep medications (up to 44.7% of men with other cancers) and antidepressants (up to three times more than at baseline), possibly associated with cancer-related fatigue and depression cluster conditions [ 92 ]. However, management of sleep and depression includes also non-pharmacological approaches.…”
Section: Discussionsupporting
confidence: 80%
“…Petrov et al (2014) found that 9.6% of their subjects used prescribed sleep medications and 11.1% used over-the-counter sleep aids [ 90 ]. Analogous to other investigations, where cancer patients presented sleep disturbances after cancer diagnosis and treatment [ 91 ], both cancer groups of our study significantly increased the consumption of sleep medications (up to 44.7% of men with other cancers) and antidepressants (up to three times more than at baseline), possibly associated with cancer-related fatigue and depression cluster conditions [ 92 ]. However, management of sleep and depression includes also non-pharmacological approaches.…”
Section: Discussionsupporting
confidence: 80%
“…Described elsewhere in detail, the KNHANES is a nationally representative survey to investigate the health and nutritional status of Koreans [4,7]. Brief information on the KNHANES is summarized as follows: since 1998, this ongoing surveillance system has been carried out every year; non-institutionalized civilians aged one and over are selected by using a multi-stage clustered probability sampling design; and three component surveys-the Health Interview, the Health Examination, and the Nutrition Surveys are conducted by well-trained medical staff [7].…”
Section: Study Populationmentioning
confidence: 99%
“…Brief information on the KNHANES is summarized as follows: since 1998, this ongoing surveillance system has been carried out every year; non-institutionalized civilians aged one and over are selected by using a multi-stage clustered probability sampling design; and three component surveys-the Health Interview, the Health Examination, and the Nutrition Surveys are conducted by well-trained medical staff [7]. Among the 63,301 respondents who were targeted for KNHANES IV and V, about 79.6% participated in surveys [4], from an initial study samples totaling from KNHANES IV and V cycles, people who were under 19 years of age or those with missing information on the history of cancer diagnosis, sleep duration, and psychological conditions (i.e., severe distress, self-reported prevalence of depression, suicidal ideation, and suicide attempt) were excluded. A final total of 34,909 subjects, including 1,042 cancer survivors and 33,867 non-cancer controls, were selected for analyses.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer survivors with Type D personality rather than non-type D personality had more pain and general discomfort 12,14 . While poor sleep quality, insomnia, and inadequate sleep time reduced the QoL 15 , high degrees of resilience contributed to a good QoL in cancer survivors 16 .…”
mentioning
confidence: 98%